Distribution strategy with product life cycle (PLC) moving to maturity stage from growth - Zaki, Shahid (Henry Stewart Talks, 2023)
Just in Time (JIT) model, Map of JIT inventory management, Inventory management and market share, Philips’ TV and Lightbulb examples